2022
DOI: 10.3332/ecancer.2022.1391
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of total oxidative stress and antioxidant capacity of brain tumour patients attending referral hospitals in Addis Ababa, 2020: a comparative cross-sectional study

Abstract: Background The exact cause of brain tumours is still unknown, but disruptions of redox balance are thought to play a significant role in all stages of brain tumour development. However, the roles of free radical imbalance at different grades of brain tumour and degree of oxidative stress before and after surgery have not been addressed in prior studies. Aim A comparative cross-sectional study was conducted to assess the redox imbalance among confirmed brain tumour patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Serum TAC is an oxidative DNA damage biomarker evaluated in different neoplastic conditions. Several lines of evidence have suggested that TAC levels are negatively associated with different types of cancers [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Serum TAC is an oxidative DNA damage biomarker evaluated in different neoplastic conditions. Several lines of evidence have suggested that TAC levels are negatively associated with different types of cancers [6][7][8].…”
Section: Introductionmentioning
confidence: 99%